Cultural-Based Spatial Management: Lesson Learnt from The Collective Intelligence of The Gayo Community, Aceh - Ade Ikhsan Kamil; Richa Meliza; Mujiburrahman Mujiburrahman; Rizki Yunanda; Shadiva Ramadhani; Galang Bayhaqie (LPPM Universitas Malikussaleh, 2024)
Cultural spaces represent a heritage passed down through generations. Today, these cultural spaces are in a worrying state, with the advent of globalization and the increasing influence of foreign cultures. Recognizing this situation, researchers aim to contribute and participate in examining the Gayo community's ability to manage these cultural spaces, as the Gayo are known for their rich cultural spaces. This study aims to explore the knowledge the Gayo people possess in managing cultural spaces and the methods by which this knowledge is passed down. Furthermore, this research intends to equip the Gayo community with insight derived from the cultural spaces that have been inherited over the years. The knowledge of these cultural spaces, when passed to future generations, becomes a foundation for the sustainability of the Gayo community's way of life. The research employs an ethnographic approach, aimed at exploring social realities in a natural context. The findings indicate that the Gayo community has a set of rules known as always, which forms the basis for determining their living spaces managed based on cultural principles. Among the Gayo community, there are five collective living spaces that have become the foundation of their way of life: Bur Perutemen, Bur Peruweren, Wih Aunen, Bur Mulo, and Hutan Keuramat.